Komunikasi Persuasif dan Sikap Pada Perundungan dalam Serial Film 13 Reasons Why - Roma Kristian Eleazar; Deddy Irwandy (LUGAS Jurnal Komunikasi, 2021)
Nowadays, the condition of bullying cases committed by teenagers in Indonesia is still high, and it remains an unresolved issue, as well as the enthusiasm of Netflix viewers in Indonesia steadily increases, where the "13 Reasons Why" series is one of the most-watched series due to it raising the bullying issue. This study aims to determine Persuasive Communication and Attitudes Toward Bullying in the 13 Reasons Why series using the elaboration likelihood model as the main theory. This study uses quantitative methodology and data collection methods through an online questionnaire with a purposive sampling technique distributed to 137 student respondents who attend schools and universities known to have a seniority culture and are located in South Jakarta. After analyzing the data using SPSS (Statistical Package for the Social Sciences) version 24, the results showed that the persuasive communication of the 13 Reasons Why series had sufficient and positive influence with a correlation coefficient of 0,543 and a contribution value of 29,5% towards bullying attitudes where the dominant path taken by respondents in receiving persuasive messages is the central route.